SHARQIY USTYURTTA O‘SUVCHI MADANIY O‘SIMLIKLARINING YOVVOYI AJDODLARIDAN BIRI AGROPYRON DESERTORUM SCHULT. NING HOZIRGI HOLATINI BAHOLASH - Ajiev, A.B.; Allamuratov, E.T. (SCIENCE and SOCIETY, 2024)
In the article Agropyron Desertorum Schult is one of the wild ancestors of cultivated plants growing in the territory of Eastern Ustyurt. analyzes were carried out to assess the current state of the plant, study its economic significance and study the ontogenesis of the plant.
Keywords: Ustyurt plateau; endemics; rare species; xenopopulation status; Agropyron desertorum